2021
DOI: 10.3390/su13126960
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Coach According to the Role of Starter or Substitute in the Final Stage of the Season

Abstract: This paper examines the athletes’ perception of their coaches according to the role of starter or substitute in the final phase of the season. The variables analyzed were: leadership style, perceived justice, competence, and support for basic psychological needs. A longitudinal study was developed, evaluating the participants at two different stages: the end of the season and seven weeks before. A total of 112 football and handball players participated in this study, 78 completing the questionnaire at the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…44,45 A recent study by De Backer et al 46 showed a positive relationship between the perception of coach support for athletes' autonomy and perceived justice. In the same line, Soto et al 47 identified that the decline in the perception of justice from coaches negatively affected the athlete's satisfaction with competence. This finding emphasizes the importance coaches' justice perceived by athletes has on satisfaction and possibly their sports performance.…”
Section: Perceived Authentic Leadership and Justice As Mediating Vari...mentioning
confidence: 95%
“…44,45 A recent study by De Backer et al 46 showed a positive relationship between the perception of coach support for athletes' autonomy and perceived justice. In the same line, Soto et al 47 identified that the decline in the perception of justice from coaches negatively affected the athlete's satisfaction with competence. This finding emphasizes the importance coaches' justice perceived by athletes has on satisfaction and possibly their sports performance.…”
Section: Perceived Authentic Leadership and Justice As Mediating Vari...mentioning
confidence: 95%
“…the most prominent lines of research is concerned with how a coach's leadership might improve or hinder players' progress (Chelladurai, 2007;Peachey et al, 2015;Soto et al, 2021). Among the various factors showing the importance of continuing to study the topic is the fact of the coach being a stakeholder who has a direct influence on the continuity or abandonment of sports practice (Back et al, 2022;Fransen et al, 2020).…”
Section: Leadership Training As a Career Differentialmentioning
confidence: 99%
“…In the same way, Giske, Stein, Johansen, and Høigaard [12] indicated in a study with elite ice hockey and handball players that satisfaction with the coach was predicted by playing time and the perception of justice. It is also convenient to mention that the variables that affect satisfaction can vary based on the different events between them during the season [11,13].…”
Section: Introductionmentioning
confidence: 99%